Insomnia as a predictor of high‐lethality suicide attempts. Issue 12 (December 2013) - Pompili, M.; Innamorati, M.; Forte, A.; Longo, L.; Mazzetta, C.; Erbuto, D.; Ricci, F.; Palermo, M.; Stefani, H.; Seretti, M. E.; Lamis, D. A.; Perna, G.; et al.
Summary Introduction Research has demonstrated that patients with insomnia are at an increased risk of experiencing suicidal ideation and/or making a suicide attempt. Objectives To evaluate the relation between insomnia and suicidal behaviour. Aims To examine factors associated with a diagnosis of insomnia in patients admitted to an Emergency Department (ED) and assessed by the psychiatrist in charge. Methods Participants were 843 patients consecutively admitted to the ED of Sant'Andrea Hospital in Rome, between January 2010 and December 2011. All patients admitted were referred to a psychiatrist. A clinical interview based on the Mini International Neuropsychiatric Interview (MINI) and a semi‐structured interview was conducted. Patients were asked about 'ongoing' suicidal ideation or plans for suicide. Results Forty‐eight percent of patients received a diagnosis of bipolar disorder (BD), major depressive disorder (MDD) or an anxiety disorder; whereas, 17.1% were diagnosed with Schizophrenia or other non‐affective psychosis. Patients with insomnia (compared to patients without insomnia) more frequently had a diagnosis of BD (23.9% vs. 12.4%) or MDD (13.3% vs. 9.5%; p < 0.001). Moreover, patients with insomnia less frequently had attempted suicide in the past 24 h (5.3% vs. 9.5%; p < 0.05) as compared with other patients, but those patients with insomnia who attempted suicide more frequently used a violent method (64.3% vs. 23.6%; p < 0.01) compared to other suicide attempters. Conclusions Our results do not support an association between insomnia and suicidal behaviour. However, suicide attempters with insomnia more frequently used violent methods, and this phenomenon should be taken into serious consideration by clinicians.